Development of Koja Cliff Tourist Attraction in The Era of The Covid-19 Pandemic in Tangerang District, Banten - Purwaganda, Achyas Hidayat; Sahlan Toro; Ria Aryani; Karlina; Steven Stefanus (The Postgraduate School of Tourism Sahid Polytechnic, 2023)
Purpose: Tourism is one of several sectors that has a big impact on increasing a country's income, foreign exchange, and employment for Indonesia. There are many types of tours offered, such as educational tours, nature tours, and many more. Unfortunately, at the end of 2019, specifically at the beginning of December, the world was shocked by the identification of the first case of the COVID-19 virus in China which has turned into a pandemic that attacks almost all countries in the world, including Indonesia. One of the sectors most affected by the pandemic is the tourism sector. The management of the tourist destination finally decided to close their place temporarily to support the government in breaking the chain of spreading the COVID-19 virus. Finally, after the implementation of the lockdown for a few months, the tourist attraction is allowed to operate again. One of the tourist attractions that has been operated again amid the pandemic is the Koja Cliff. The purpose of this research is to find out the development of the Koja Cliff tourist attraction in Tangerang District, Banten in the era of the pandemic. Research method: The research used qualitative methods and purposive sampling as the sampling technique. Data were collected by interview, observation, and documentation. Result and discussion: The results of the study explain that the development of the Koja Cliff tourist attraction so far can be said has not been good enough Implication: the Koja Cliff tourist attraction manager already has some plans for future to develop the tourism objects which will focus on the Cliffs of the Koja Cliffs and surrounding attractions Keywords: Tourist, Tourism Development, Koja Cliff